Neutronic Evaluation of a Liquid Salt–Cooled Reactor Assembly. (3rd August 2017) - Gentry, Cole; Maldonado, G. Ivan; Chvala, Ondrej; Petrovic, Bojan
Abstract: This study presents a thorough parametric neutronic analysis of a plate-based tristructual isotropic (TRISO) fuel particle bearing liquid salt–cooled reactor assembly. The analyses presented investigated the effects of altering fuel enrichment, packing fraction, plate region thicknesses, assembly structure thicknesses, assembly size, numbers of plates per assembly, use of burnable poison materials, replacement of assembly and plate carbon material with silicon carbide, and use of uranium nitride fuel kernels. The effects or trends observed included reactivity behavior, discharge burnup, cycle length, and other key design parameters such as moderator temperature coefficients, coolant density coefficients, control blade worth, and impacts upon power peaking (i.e., power and flux distributions). This study is based upon two-dimensional lattice physics calculations involving the SERPENT 2 code and by using the nonlinear reactivity model as a reasonable tool for predicting discharge burnup. The reported results show that the system's reactivity can be significantly altered by varying these design parameters, thus providing a starting point for future design optimization studies, and it is understood that future studies will need to be expanded to equilibrium full core analysis for more complete and accurate design and safety assessments, which is also a work in progress.